2008
DOI: 10.1063/1.2968129
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear characteristics of T-branch junctions: Transition from ballistic to diffusive regime

Abstract: Nonlinear electrical characteristics of nanostructured T-branch junctions (TBJs) made of two-dimensional electron gas in an InGaAs∕InAlAs heterostructure were studied by a systematic variation of both the device size and the operating temperature. We have found that two distinct mechanisms are responsible for the electronic transport in TBJs and their resulting nonlinear characteristics, namely, the nonlinear ballistic effect at low applied voltages and the intervalley transfer at high voltages. Detailed exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…As in the previous TBJs, it is the presence of the vertical branch and the associated surface charges which leads to different values of V C in each of the structures. Like in the case of the experimental results [Irie et al, 2008] we found that the down-bending behaviour of V C is stronger for shorter junctions. This result is expected because of the more ballistic character of transport in shorter structures, but our results indicate that surface charges and the presence of the vertical branch also play a role.…”
Section: Influence Of the Horizontal Branchsupporting
confidence: 65%
See 2 more Smart Citations
“…As in the previous TBJs, it is the presence of the vertical branch and the associated surface charges which leads to different values of V C in each of the structures. Like in the case of the experimental results [Irie et al, 2008] we found that the down-bending behaviour of V C is stronger for shorter junctions. This result is expected because of the more ballistic character of transport in shorter structures, but our results indicate that surface charges and the presence of the vertical branch also play a role.…”
Section: Influence Of the Horizontal Branchsupporting
confidence: 65%
“…6(c). The nonlinear effect can be enhanced by decreasing the temperature of operation because the reduction in the number of scattering mechanisms [Irie et al, 2008]. The negative values of V C have been reproduced by Monte Carlo simulations of TBJs [ Fig.…”
Section: Overview and Working Principlementioning
confidence: 75%
See 1 more Smart Citation
“…One class of such ballistic devices is nanoscale three-branch junctions (TBJs) fabricated in 2-dimensional electron gas (2DEG) heterostructures [2,3]. Because of the extremely small internal capacitance of the TBJ, its frequency response is free from the RC charging time limitations, contrary to the conventional electron devices.…”
Section: Introductionmentioning
confidence: 99%
“…The TBJ is a 3-terminal device that exhibits a nonlinear transfer curve originated from the ballistic electron transport [3]. It has been shown that the nonlinear response makes the TBJs work as rectifiers or logic gates [1].…”
Section: Integrated System For the Generation And Detection Of The Pimentioning
confidence: 99%